A new genus of Antiliocorini from Baja California, Mexico (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae: Rhyparochrominae) - Peredo, Luis Cervantes; Brailovsky, Harry (Zootaxa, 2012)
A new genus of Antillocorini, Pulmomerus, and a new species Pulmomerus levatus from Baja California Sur aredescribed. This species with reduced hemelytra is characterized by the presence of spines on the fore femora, the veryelevated connexiva, the absence of metathoracic wings, and a peculiar and unique spermatheca. Specimens were foundunder leaf litter of Ficus palmeri, which represents another record of Rhyparochromidae associated with figs in Mexico, and a probably endemic species from Cabo Pulmo National Park.